MANAJEMEN PENDIDIKAN PADA PONDOK PESANTREN AL HIKAMUSSALAFIYAH PURWAKARTA - Ike Nilawati Rohaenah; Sahudi; Nur Wadjah Ahmad; Andewi Suhartini (Pascasarjana Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2020)
This study aims to determine the management of educational planning at the Al Hikamussalafiyah Islamic boarding school, Purwakarta. Qualitative research methods, data obtained through observation, documentation and interviews. Respondents in this study were extracted from informants who have a key role in planning management as decision makers in the educational process, namely the caregivers of Islamic boarding schools, principals of madrasas, religious teachers and board of Islamic boarding schools using narrative presentation. The issues discussed in this study reveal how education management is viewed from management of Islamic boarding school education planning. The urgency of this research is that if a boarding school does not make management planning, it will have fatal consequences. Because there is no short, medium, and long term planning to guide the work and teaching guidelines in Islamic boarding schools. The results of this study reveal that: The management of the Al-Hikamussalafiyah Islamic boarding school education planning was designed Management education planning management: Having a vision and mission. purpose, order. organizational structure, infrastructure, work plan. The leadership of the Al Hikamussalafiyah Islamic boarding school